A new species of the genus Gortyna Ochsenheimer, 1816 from China, with notes on the larval feeding habits (Lepidoptera, Noctuidae, Noctuinae: Apameini) - Wu, Jun; Yang, Mao-Fa; Han, Hui-Lin (Zootaxa, 2022)
A new species of the genus Gortyna Ochsenheimer, 1816, G. guizhouensis sp. n., is described from Guizhou Province, China. Adults and genitalic structures of the new species and related species are illustrated. Observations of feeding habits and host plant of the larva are also provided.